The Experiences and Practice of Adult Educators in Addressing Spirituality within the Workplace: An Empirical Study - Janet Groen (Adult Education Research Conference, 2002)
This paper reports on life history research with 5 adult educators who work in a variety of workplace contexts. This research examined the experience and practice of these adult educators, as they were involved in the growing phenomenon of addressing spirituality within their workplace settings.